Advances in experimental social psychology. - Olson, James M.; Zanna, Mark P. (Academic Press, 2014)
Advances in Experimental Social Psychology continues to be one of the most sought after and most cited series in this field. Containing contributions of major empirical and theoretical interest, this series represents the best and the brightest in new research, theory, and practice in social psychology. The present volume, number 50, features articles on the evolution of human mating strategies, free will in social psychology, social psychology and the fight against AIDS, and more.One of the most sought after and most cited series in this fieldContains contribut.